Improving Indonesia's Food Statistics through the Area Sampling Frame Method - Kadir Ruslan (Center for Indonesian Policy Studies (CIPS), 2019)
This paper highlights shows how differing methods of data collection from various government bodies have led to an erroneous overestimations in Indonesia's domestic rice supplies. The data, which is used in the decision making process for food policies, have impacted how much consumers pay for rice. The paper proposes modern data collection methods to capture a more accurate picture of staple food availability, and the challenges these proposed methods would face if implemented.
Keywords: 330; food statistics; bps; area sampling frame method; kadir ruslan; data accuracy; rice and secondary crops; rice; production; asf; bulog